Assessment of Biomedical Waste Management Practices and Paramedical Staff Knowledge and Attitude at Healthcare Facilities in Lahore, Pakistan : Biomedical Waste Management Practices - Riaz, Assia; Majeed, Fatima; Sabir, Samia; Imran, Muhammad; Fatima, Syeda Nida; Shahbaz, Mehreen; Saleem, Javeria; Shahbaz, Ferheen; Tahir, Muhammad Navid; Amjad, Aaisha (Pakistan Journal of Health Sciences, 2023)
Healthcare waste refers different natures of wastes, biological, and non-biological which are useless& do not desired to re-use again. Healthcare (Biomedical) waste can be defined that all waste generates from healthcare settings. Objective: To analyze the awareness, attitudes & Para medical’s work practically related to the management of BMW at Public, Private, DHQ and THQ Hospitals, RHC and BHU of Lahore, Punjab. Methods: The methodology was cross-sectional and consisted on the data (survey based) and talk to the heads of the Institutions, persons concerned with waste (handling and transportation). The data about medical waste management were taken from ten HCFs. Results: The results showed that <50% has knowledge about categories, color coding and different wastes that are not included in Biomedical Waste Management Rules, 2016. Attitude shows good results. >50% has faulty practice regarding bio medical waste. The findings about the awareness & practice about the management of waste among Intern Nurses and sanitary workers were poor, periodic training and their evaluation is mandatory for better outcome. Total percentage of the knowledge items was 57%. The attitude percentage was 44%. The overall level of practice was considered unsafe because only 9.4% respondent who practice always during waste management. Conclusions: Research revealed the improper practices, irregularities, and shortcomings in the overall system of the WM. The study found inconsistencies during waste management in hospitals are generally because of low amount of financial resources, poor awareness & trainings at the administrative level.